LATERAL PERFORMANCE OF COLD-FORMED STEEL-PLYWOOD COMPOSITE WALLS - saputra, muhamadd andy harjuna setahadi; S, Siswosukarto; A, Awaludin (Kohesi: Jurnal Sains dan Teknologi, 2024)
Traditional brick walls face notable limitations, particularly in their weight and vulnerability to lateral forces, which can lead to significant damage under seismic conditions. This study investigates Cold-Formed Steel (CFS) and plywood composite walls as an alternative solution, focusing on lateral load performance. Laboratory tests on CFS-plywood wall specimens, both with bracing and without bracing, allowed for a comparison of lateral load capacity, deflection, and crack development. The findings reveal that bracing improves lateral stability significantly, enabling the braced walls to support a peak load of 14.127 kN compared to 13.77 kN in unbraced walls. Additionally, bracing reduces deflection and distributes cracks more evenly, presenting CFS-plywood composite walls as a lightweight, resilient choice for earthquake-resistant structures.